The effectiveness of dexamethasone on the prognosis of dialysis patients with severe COVID-19 - Toçoglu,Aysel (2021)
SUMMARY OBJECTIVE: This study aimed to investigate the effectiveness of dexamethasone in dialysis patients with COVID-19 and whether it predicts mortality. METHODS: This is a comparative cross-sectional study of 113 consecutive patients with COVID-19 with severe pneumonia signs. The patients were divided into two groups according to the use of dexamethasone treatment: group 1 (n=45) included patients who were treated with dexamethasone and group 2 (n=68) who did not receive dexamethasone. RESULTS: The mean age of both groups was 67.0±10.6 and 67.2±13.0 years, respectively (p=0.947). With respect to demographic and laboratory findings, there were no significant differences between the two groups (p>0.05). The hospitalization time of patients in group 1 was longer than that in group 2 (11 [7–17] days vs. 8 [5.3–14] days, p=0.093]. The 28-day survival rate was 54.2% in the group receiving dexamethasone treatment and 79.5% in the group not receiving dexamethasone treatment (p=0.440). CONCLUSION: Dexamethasone did not reduce mortality rates and the requirement for intensive care unit in dialysis patients with COVID-19. Larger prospective randomized clinical trials are required to associate personalized medicine with the corticosteroid treatment to select suitable patients who are more likely to show a benefit.